Depositional environments and maturity evaluated by biomarker analyses of sediments deposited across the Cenomanian–Turonian boundary in the Yezo Group, Tomamae area, Hokkaido, Japan. (January 2017) - Ando, Takuto; Sawada, Ken; Nakamura, Hideto; Omatsu, Keita; Takashima, Reishi; Nishi, Hiroshi
Abstract : Biomarker analyses for evaluating maturity of organic matter and depositional environments such as redox conditions, were performed in sediments across the Cenomanian–Turonian boundary (CTB) in the Saku Formation of the Yezo Group distributed along the Shumarinai‐gawa River and the Omagari‐zawa River, both in the Tomamae area, Hokkaido, Japan. Maturity indicators using steranes and hopanes, show that organic matter in sediments from the Shumarinai‐gawa and Omagari‐zawa sections are of lower maturity than those from the Hakkin‐gawa section (Oyubari area). Moreover, the ββ hopane ratios clearly show that the maturity of the Shumarinai‐gawa samples is lower than that of the Omagari‐zawa samples. These variations in the maturity of organic matter presumably reflect the difference in their burial histories. The results for the pristane/phytane (Pr/Ph) ratios suggest that the Shumarinai‐gawa samples were deposited under dysoxic to anoxic environments across the CTB, while the depositional environments of the Omagari‐zawa samples were relatively oxic. By another paleoredox indicator using C35 homohopanoids including a homohopene index (HHenI), higher values are observed in the Shumarinai‐gawa section, particularly in the horizons of the preceding period and an early stage of the first negative shift phase and the latest oceanic anoxic event 2 (OAE2) interval. These results suggest that the Shumarinai‐gawa samples record dysoxic to anoxic environments across the CTB. In contrast, the signals for the C35 homohopanoid index values show a relatively oxic condition in the Omagari‐zawa section. The trends of stratigraphic variations in redox conditions are different from those in the OAE2 interval in the proto‐Atlantic and Tethys regions as reported previously. Hence, the redox variations in the Tomamae area were basically related to a local environmental setting rather than global anoxia. However, the prominent anoxic emphasis observed in the HHenI profile of the Shumarinai‐gawa section can be a distinctive, and possibly global, event in the North‐West Pacific just before the OAE2. Abstract : Biomarker analyses for evaluating maturity of organic matter and depositional environments such as redox conditions were performed in sediments across the Cenomanian–Turonian boundary (CTB) in the Saku Formation of the Yezo Group distributed along the Shumarinai‐gawa and Omagari‐zawa Rivers in the Tomamae area, Hokkaido, Japan. Maturity indicators using steranes and hopanes, show that organic matter in sediments from the Shumarinai‐gawa and Omagari‐zawa sections are of lower maturity than those from the Hakkin‐gawa section (Oyubari area). The redox variations in the Tomamae area were basically related to local environmental setting rather than global anoxia. However, the prominent anoxic emphasis observed in the HHenI profile of the Shumarinai‐gawa section can be a distinctive and possibly global event in the North‐West Pacific just before the OAE2.